Opening the networks with Parlay standards and aspects behind the APIs. - Moerdijk, A.-J (IEEE Network : the magazine of global information exchange)
Recently there has been an enormous increase in efforts to open up telecommunication networks for application development. In opening up the network, new business models emerge where applications can be developed and provided by enterprises outside the traditional network operator domain. This new business model, combined with the fact that applications can be built using standardized API with off-the-shelf IT technology and tools, will result in new innovative applications that will hit the market with drastically reduced development cycles. This article provides an overview of the Parlay/OSA initiatives concerning the specification of a set of open standardized API. Furthermore, the article outlines some architectural aspects that are implied and implicitly contained in the Parlay/OSA specifications. These are critical for understanding the implications when allowing access to the network via Parlay/OSA. The article then outlines different types of applications that can be built using Parlay/OSA. Finally, we conclude with an analysis of the future of Parlay/OSA.